(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article details the factors for the development of educational competencies for teachers of military education up to the upcoming call through problematic educational technologies and the pedagogical aspects of the development of educational activities of students of military educational faculties through problematic educational technologies.